Mechanisms for Maintaining Eukaryotic Replisome Progression in the Presence of DNA Damage - Guilliam, Thomas A. (Frontiers in Molecular Biosciences, 2021)
The eukaryotic replisome coordinates template unwinding and nascent-strand synthesis to drive DNA replication fork progression and complete efficient genome duplication. During its advancement along the parental template, each replisome may encounter an array of obstacles including damaged and structured DNA which impede its progression and threaten genome stability. A number of mechanisms exist to permit replisomes to overcome such obstacles, maintain their progression, and prevent fork collapse. A combination of recent advances in structural, biochemical, and single-molecule approaches have illuminated the architecture of the replisome during unperturbed replication, rationalised the impact of impediments to fork progression, and enhanced our understanding of DNA damage tolerance mechanisms and their regulation. This review focusses on these studies to provide an updated overview of the mechanisms which support replisomes to maintain their progression on an imperfect template.